DESIGN OF DOLPHIN STRUCTURE FOR LNG TERMINAL IN TUDI BAY, NORTH GORONTALO - Listya Prasadini - NIM 15514053, Bella
Indonesia is one of the exporters in the LNG (Liquefied Natural Gas) international trade. Gorontalo is taking part in LNG export to India so that LNG loading and unloading dock is planned in Tudi Bay, North Gorontalo District, Gorontalo Province using dolphin type and deck on pile structure for supporting the export activities. The dock structure consists of loading platform, breasting dolphin, mooring dolphin, and trestle. The scope of the final project includes an explanation of the planning design criteria, load calculation on structure, determination of structural dimensions, structural modelling, structural reinforcement design, and geotechnical analysis. Dolphin design refers to the British Standard, structural design refers to SNI 1729: 2015 for steel and SNI 2847: 2013 for concrete. Structural modelling is carried out using SAP2000 software to determine the reability of the plan structure against the working load. The results of modeling are Unity Check Ratio (UCR), structural deflection, force in beams and plates, and base reactions. The planned LNG dock structure produces UCR between 0.8 and 1.0 with beams and piles deflection comply the deflection permit limit. The internal force is used for reinforcing concrete structures and base reaction is used to determine the piling depth of structure foundation. Based on geotechnical analysis result, the structural foundation for loading platform, breasting dolphin, mooring dolphin, and trestle is piled until 33 m, 39 m, 27 m, and 27 m below the seabed.